Fatores de permanência de mulheres no casamento em situação insatisfatória: um estudo compreensivo - Barboza, Silvana Negro (2009)
The objective of this work was to understand the underlying reasons which lead a woman to maintain an unsatisfactory relationship. In order do achieve this goal, some of them were hereby presented using qualitative research carried out with five subjects whose age varied between 37 and 59 years old, separated after having lived within an unsatisfying relationship, according to their own statements. The data was gathered by the use of semi structured interviews, as well as by constructing a genogram and a timeline. Based on the analysis of the narrative outcomes of the interviewed women, categories and sub categories which allow selecting some of the reasons which led those women to remain married in spite of the reported dissatisfaction were devised. All motives presented by them such as: gender, beliefs concerning marriage and separation, individuality needs, conjugal experience and transgenerationality are very relevant and, at times, easily perceived both by the women and by the other people of their relationship. All but the transgenerationality, which is not so easily visible, and except when there is an especial attention to their antecessor stories (mother and grandmother) and to their own stories. In those cases it was possible to identify and notice to what extent the same story is repeated. In conclusion, it is important to widen the look to the issue of transgenerationality, when women in such situation search for help, in order to help them realize that sometimes the guilt they feel are not their own, but inherited from some other family member, like a secret to be kept